Integrative Approaches to Muscle Recovery: The Impact of Protein, Micronutrients, and Cold-Water Immersion on Performance and Health - Goliszek, Zofia; Szarłowicz, Jakub; Mazur, Michał; Waz, Dorota; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła, Sebastian (Quality in Sport, 2025)
Introduction and Purpose Muscle regeneration, enhanced performance, and overall health improvement rely on effective strategies that support recovery processes by integrating nutritional and physiological approaches. This paper evaluates the synergistic effects of protein, micronutrients, and cold-water immersion (CWI) in the context of muscle regeneration, inflammation reduction. Materials and Methods A detailed analysis of 22 peer-reviewed from scientificdatabases, including PubMed, focused on the impact of protein intake, and the physiological benefits of cold-water immersion. Practical applications were developed, and the latest trends in recovery strategies were discussed. Results Protein intake, stimulates muscle protein synthesis (MPS) and counteracts sarcopenia. Micronutrients reduce oxidative stress, support immune functions, and accelerate recovery. CWI decreases inflammation and delayed onset muscle soreness (DOMS). The integrated application of these strategies yields better outcomes in muscle recovery and health compared to single interventions. Conclusion Combining high-quality protein, essential micronutrients, and cold-water immersion represents a comprehensive approach to optimizing recovery and health. The findings support the use of these strategies across various population groups, including athletes, older adults, and clinical patients. Further research is needed to personalize these interventions and assess their long-term effects.